Neighbour replica affirmative adaptive failure detection and autonomous recovery - Mohd Noor, Ahmad Shukri (2012)
High availability is an important property for current distributed systems. The trends of current distributed systems such as grid computing and cloud computing are the delivery of computing as a service rather than a product. Thus, current distributed systems rely more on the highly available systems. The potential to fail-stop failure in distributed computing systems is a significant disruptive factor for high availability distributed system. Hence, a new failure detection approach in a distributed system called Affirmative Adaptive Failure Detection (AAFD) is introduced. AAFD utilises heartbeat for node monitoring. Subsequently, Neighbour Replica Failure Recovery(NRFR) is proposed for autonomous recovery in distributed systems. AAFD can be classified as an adaptive failure detector, since it can adapt to the unpredictable network conditions and CPU loads. NRFR utilises the advantages of the neighbour replica distributed technique (NRDT) and combines with weighted priority selection in order to achieve high availability, since automatic failure recovery through continuous monitoring approach is essential in current high availability distributed system. The environment is continuously monitored by AAFD while auto-reconfiguring environment for automating failure recovery is managed by NRFR. The NRFR and AAFD are evaluated through virtualisation implementation. The results showed that the AAFD is 30% better than other detection techniques. While for recovery performance, the NRFR outperformed the others only with an exception to recovery in two distributed technique (TRDT). Subsequently, a realistic logical structure is modelled in complex and interdependent distributed environment for NRDT and TRDT. The model prediction showed that NRDT availability is 38.8% better than TRDT. Thus, the model proved that NRDT is the ideal replication environment for practical failure recovery in complex distributed systems. Hence, with the ability to minimise the Mean Time To Repair (MTTR) significantly and maximise Mean Time Between Failure (MTBF), this research has accomplished the goal to provide high availability self sustainable distributed system.